DOI: 10.31274/rtd-180813-4355
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of photosynthetically active radiation to apparent photosynthetic distributions within soybean canopies

Abstract: INFORMATION TO USERS This material was produced from a microfilm copy of the original document. While the most advanced technological means to photograph and reproduce this document have been used, the quality is heavily dependent upon the quality of the original submitted. The following explanation of techniques is provided to help you understand markings or patterns which may appear on this reproduction. 1.The sign or "target" for pages apparently lacking from the document photographed is "Missing Page(s)". … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 79 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…According to a number of authors (Harris, 1973;Dube et al, 1974;Neumann et al, 1974;Turner and Incoll, 1971), the photosynthetic rate was not affected below a critical resistance level but decreased rapidly if the stomatal resistance was greater than the critical resistance. Hatfield (1975) reported that reduced COg uptake occurred through stomatal closure, as evidenced by increased stomatal resistance. Brown and Rosenberg (1970) have shown that for sugarbeets, small decreases in soil-water potential may lead to partial stomatal closure and thereby re duce the photosynthetic rate.…”
Section: Importance Of Stomatal Diffusion Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…According to a number of authors (Harris, 1973;Dube et al, 1974;Neumann et al, 1974;Turner and Incoll, 1971), the photosynthetic rate was not affected below a critical resistance level but decreased rapidly if the stomatal resistance was greater than the critical resistance. Hatfield (1975) reported that reduced COg uptake occurred through stomatal closure, as evidenced by increased stomatal resistance. Brown and Rosenberg (1970) have shown that for sugarbeets, small decreases in soil-water potential may lead to partial stomatal closure and thereby re duce the photosynthetic rate.…”
Section: Importance Of Stomatal Diffusion Resistancementioning
confidence: 99%
“…Hark and Rampage, Hatfield (1975) concluded that the stomatal resistance increased with increasing depth in the canopy.…”
Section: Lightmentioning
confidence: 99%
See 2 more Smart Citations
“…Corn leaf photosynthesis rates were monitored with a carbon-14 carbon dioxide uptake technique developed for field use by Shimshi (1969) and by Incoll and Wright (1969). The method used in our experiments is described by Hatfield (1975) and by Naylor and Teare (1975). The leaf exposure cham ber was modified from that described by Hatfield by attaching it to the handles of a single hole punch for convenience in holding the chamber on 14 the leaf.…”
Section: Photosynthesis Studiesmentioning
confidence: 99%